AWARENESS OF NOVEL H1N1 PANDEMIC INFLUENZA AMONG NON-MEDICAL PERSONNEL, MEDICAL STUDENTS & MEDICAL PROFESSIONALS: Novel H1N1 Pandemic Influenza - Usman, Brig Javaid; Shah, Aun Raza; Azhar, Muhammad; Ali, Muhammad Zeeshan; Bilal, Mohammad; Khan, Rizwan Ullah; Raees, Afrah; Hussain, Shehzad; Hussain, Shehzad (Pakistan Armed Forces Medical Journal, 2010)
Objective: To study the awareness of swine flu among general population, medical students and medical professionals Study Design: Descriptive study. Place and Duration of Study: Study was carried out in the department of Pathology (Microbiology), Army Medical College, the Military Hospital (MH) and Combined Military Hospital, Rawalpindi, from 17th January 2010 to 24th January 2010. Materials and Methods: A total of 519 people were included in this study, 228 were medical students, 181 were doctors and 110 were non health care professionals. A questionnaire with closed questions regarding the awareness of the basics of swine flu was required to be filled by all participants